Optimization of the protoplast fusion conditions of Saccharomyces cerevisiae and Pichia stipitis for improvement of bioethanol production from biomass - Shalsh, Fawzia Jassim; Ibrahim, Noor Azlina; Arifullah, Mohammed; Meor Hussin, Anis Shobirin (A N S I Network, 2016)
Bioethanol production using lignocellulosic biomass has gained increased attention because of the abundant supply of this biomass. Saccharomyces cerevisiae is a commonly used microorganism for ethanol production. Nevertheless, S. cerevisiae can not ferment xylose, the second most abundant sugar in plant tissues. In this study, protoplast fusion with the xylose-fermenting yeast Pichia stipitis was performed to improve bioethanol production from biomass. The protoplast formation of S. cerevisiae and P. stipitis (ATCC 58785) cells was achieved using zymolase 20T. The effects of zymolase concentration, enzymatic treatment time and osmotic stabilizers were further investigated. The optimal parameter for the protoplast release of S. cerevisiae and P. stipitis included 500 μg μL–1 zymolase for 60 min and 750 μg μL–1 zymolase for 120 min, respectively. The maximum protoplast formation ratios were 98.48 and 84.42% for S. cerevisiae and P. stipitis, respectively, with 1 mol L–1 sorbitol as the osmotic stabilizer. About 4×106 mL–1 protoplasts from S. cerevisiae and P. stipitis were isolated. Protoplast fusion frequency was determined using polyethylene glycol (PEG) as fusogen. The optimized fusion conditions of S. cerevisiae protoplasts with P. stipitis required 35% (w/v) PEG 6000, 10 mM CaCl2 level and 30 min of fusion time. The protoplast fusion rate was 52.21% under the optimized fusion condition.